Validation of pharmacokinetic model for quizartinib quantified by UPLC-MS/MS in patients with FLT3-ITD negative newly diagnosed acute myeloid leukemia - Antonio Solana-Altabella; Carles Iniesta-Navalón; Maria Chovi-Trull; Rebeca Rodriguez-Veiga; Marina Lopez-Nogueroles; David Martínez-Cuadrón; Mayte Gil-Candel; Laura Torres-Miñana; Evelyn Acuña-Cruz; Isabel Cano-Ferri; Blanca Boluda; Irene Navarro-Vicente; et al. (European Journal of Clinical Pharmacology, 2025)
Purpose Quizartinib pharmacokinetics in FLT3-ITD negative acute myeloid leukemia (AML) remain largely unexplored. This study aims to validate a population pharmacokinetics model (popPK) for quizartinib in plasma samples of FLT3-ITD negative AML patients. To do so, an ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) method has been developed and validated for the quantification of quizartinib. Methods Plasma samples were collected from FLT3-ITD negative newly diagnosed AML patients undergoing quizartinib therapy at induction in the QUIWI phase II clinical trial [NCT04107727, PETHEMA group] between March 2020 and February 2022. The UPLC-MS/MS method was developed and validated. A previously described popPK model was validated using external validation techniques and implemented using the software NONMEM v7.5. Results The developed UPLC-MS/MS method demonstrated high accuracy and precision with a linear range of 6 to 200 ng/mL, with relative standard deviation between 3–11 and accuracy of 88–97% from nominal values. The external validation of the quizartinib popPK model showed minimal bias at the population level (MdPE: -9.86%; ME: 0.50 ng/mL, p = 0.964), but moderate imprecision (MdAPE: 32.28%) and suboptimal accuracy (F20: 24.5%; F30: 43.4%). Individual predictions improved performance, with negligible bias (MdPE: -0.50%), acceptable precision (MdAPE: 11.27%), and F20 (64.2%) and F30 (77.4%) exceeding predefined thresholds. Visual predictive checks confirmed adequate prediction of median concentrations, though some deviations occurred at extremes. Conclusion This study presents a replicable UPLC-MS/MS method for the determination of quizartinib in plasma. The validated popPK model can be used to optimize dosing strategies in future clinical studies.

Cortical volumetry and longitudinal cognitive changes in Parkinson’s disease: insights from the COPPADIS cohort - Tania Álvarez-Avellón; Carmen Solares; Juan Álvarez-Carriles; Pablo Franco-Rosado; Patricia Diaz-Galvan; Diego Santos-García; Pablo Mir; Manuel Menéndez-González; Astrid Adarmes Daniela; Almeria Marta; Maria Gema Alonso Losada; Araceli Alonso Cánovas; et al. (Brain Imaging and Behavior, 2025)
Cognitive decline is a major non-motor symptom in Parkinson’s disease (PD), often linked to brain atrophy. This study examines the relationship between cortical atrophy and age groups in predicting cognitive decline in PD over five years. 188 PD patients from the COPPADIS cohort were stratified by age: young (30–55 years, N = 47), middle-aged (56–65 years, N = 59), and older adults (66–75 years, N = 82). Baseline cortical volume was assessed using T1-weighted MRI, and cognitive decline was evaluated using the annual rate of change of the Parkinson’s Disease-Cognitive Rating Scale (PD-CRS). Parametric or non-parametric tests were applied to evaluate group differences. Main analyses consist of several multiple regression analyses to examine associations between baseline brain atrophy and cognitive decline by age group. Older adults exhibited significantly greater cognitive decline in comparison to the younger age groups in the three compose scores of the PDCRS -Fronto-subcortical (H(2) = 41.08, p < 0.001), Posterior Cortical (H(2) = 22.03, p < 0.001), and Total(H(2) = 41.13, p < 0.001). Higher educational level has a significant positive effect on older adults, specifically for working memory performance, delayed verbal memory and the fronto-subcortical composed score. Multiple regression models underscored the predictive value of the bilateral hippocampus, bilateral medial orbitofrontal cortex, right precuneus, and right isthmus cingulate gyrus, together with being an older adult or having a higher education. MRI measures, age, and education predict cognitive decline in PD. Longitudinal assessments are essential for refining atrophy-cognition correlations and optimizing patient stratification.

Smart polymers and smartphones for Betalain measurement in cooked beetroots - María Gaona-Ruiz; Jorge Lucas Vallejo-García; Ana Arnaiz; Carlos Sedano-Labrador; Miriam Trigo-López; Ana Rodríguez; Celia Carrillo; Saúl Vallejos (Food Chemistry, 2024)

Feather mites at night: an exploration of their feeding, reproduction, and spatial ecology - María del Mar Labrador; Jorge Doña; David Serrano; Roger Jovani (Ecology, 2022)

Rapid and Biosecure Diagnostic Test for Tuberculosis - Juan Garberi; Jorge Labrador; Federico Garberi; Juan Ezequiel Garberi; Julián Peneipil; Miguel Garberi; Luis Scigliano; Alcides Troncoso (Cell Biochemistry and Biophysics, 2013)